Bacterial secretion systems contribute to rapid tissue decay in button mushroom soft rot disease - Philipp Wein; Katharina Dornblut; Sebastian Herkersdorf; Thomas Krüger; Evelyn M. Molloy; Axel A. Brakhage; Dirk Hoffmeister; Christian Hertweck (mBio, 2023)
ABSTRACT The soft rot pathogen Janthinobacterium agaricidamnosum causes devastating damage to button mushrooms (Agaricus bisporus), one of the most cultivated and commercially relevant mushrooms. We previously discovered that this pathogen releases the membrane-disrupting lipopeptide jagaricin. This bacterial toxin, however, could not solely explain the rapid decay of mushroom fruiting bodies, indicating that J. agaricidamnosum implements a more sophisticated infection strategy. In this study, we show that secretion systems play a crucial role in soft rot disease. By mining the genome of J. agaricidamnosum, we identified gene clusters encoding a type I (T1SS), a type II (T2SS), a type III (T3SS), and two type VI secretion systems (T6SSs). We targeted the T2SS and T3SS for gene inactivation studies, and subsequent bioassays implicated both in soft rot disease. Furthermore, through a combination of comparative secretome analysis and activity-guided fractionation, we identified a number of secreted lytic enzymes responsible for mushroom damage. Our findings regarding the contribution of secretion systems to the disease process expand the current knowledge of bacterial soft rot pathogens and represent a significant stride toward identifying targets for their disarmament with secretion system inhibitors. IMPORTANCE The button mushroom (Agaricus bisporus) is the most popular edible mushroom in the Western world. However, mushroom crops can fall victim to serious bacterial diseases that are a major threat to the mushroom industry, among them being soft rot disease caused by Janthinobacterium agaricidamnosum. Here, we show that the rapid dissolution of mushroom fruiting bodies after bacterial invasion is due to degradative enzymes and putative effector proteins secreted via the type II secretion system (T2SS) and the type III secretion system (T3SS), respectively. The ability to degrade mushroom tissue is significantly attenuated in secretion-deficient mutants, which establishes that secretion systems are key factors in mushroom soft rot disease. This insight is of both ecological and agricultural relevance by shedding light on the disease processes behind a pathogenic bacterial-fungal interaction which, in turn, serves as a starting point for the development of secretion system inhibitors to control disease progression.